Improving Students Writing Skills Explanation Text using Animated Video - Widya Puspita; Teti Sobari; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2023)
This study focuses on the influence of an animated video on students' ability to write explanation text. This research uses descriptive qualitative research method. The purpose of this study is to find out whether the animated video used can help students improve their explanation text writing skills and see the differences in students' abilities before and after using animated videos in Indonesian language learning. The subjects in this study came from 20 students of class VII A at MTs Pasundan Cimahi, and the objects in this study were obtained from the results of the pre-test and post-test of students in writing explanation texts before and after using animated videos. The results of the analysis show that based on the output table data 1, there is no decrease from the pre test value to the post test value. Then between the results of the explanation text writing test for the pre-test and post-test there were 20 positive data (N), meaning that 20 students experienced an increase in the results of the explanation text writing test. Furthermore, in output table 2, it shows that there is a difference between the results of the explanation text writing test for pre-test and post-test, meaning that there is an influence of using animated videos on the learning outcomes of writing explanation texts for class VII A students. Animated videos are one of the learning media that can be used to improve the skills of writing explanation text.Â